Optimization of DNA isolation from hop cones and pellets for microsatellite analysis - Tacer, Matic (Hmeljarski bilten, 2025)
Reliable identification of hop (Humulus lupulus L.) cultivars is important for quality control and authentication in the brewing industry. DNA-based methods provide a powerful tool for this purpose, but isolation of high-quality DNA from processed hop materials such as cones and pellets can be challenging due to the presence of PCR inhibitors, including polyphenols, polysaccharides, and bitter acids. In this study we compared four cetyltrimethylammonium bromide (CTAB)-based DNA extraction protocols for hop cones and pellets, with the aim of improving yield and purity of DNA used for microsatellite genotyping. The tested methods included the standard CTAB protocol, CTAB supplemented with polyvinylpyrrolidone (PVP40), CTAB with PVP40 and activated charcoal, and CTAB with PVP10 and liquid nitrogen grinding. Additionally, a hexane pre-treatment step was evaluated with the aim to reduce the amount of PCR inhibitory compounds. DNA quality was assessed using NanoVue, Qubit, and agarose gel electrophoresis. Agarose gels showed intact high-molecular-weight DNA with minor RNA traces. Microsatellite genotyping confirmed consistent allele profiles across the first three extraction methods, thus confirming the suitability of CTAB-based methods for reliable hop genotyping.
Keywords: CTAB; DNA extraction; genotipizacija; genotyping; hmelj; hop; Humulus lupulus; izolacija DNA